The Influence of Public Literacy Regarding Sharia Financing on the Growth of MSMEs in Pademawu Pamekasan - Ach. Jailani; Abdur Rohman (Al-Abqori: Journal of Islamic Thought Studies, 2026)
Sharia financial literacy plays a crucial role in increasing access to financing for Micro, Small, and Medium Enterprises (MSMEs) in Madura. This study aims to analyze the influence of public literacy regarding Sharia financing on the growth of MSMEs, focusing on understanding sharia concepts and the factors that support or hinder MSME access to the Sharia-based financial system. This study uses a descriptive qualitative approach with a literature review method to analyze how Sharia financial literacy influences access to Sharia financing for MSMEs in Madura. This approach was chosen because the research focuses on an in-depth understanding of social phenomena. Data were collected from various scientific sources such as journals, academic books, and research reports. The literature reviewed includes the concept of Islamic financial literacy, as well as an analysis of the gap in access to Islamic finance in terms of understanding, service availability, and ease of access, as well as public trust in Islamic financial institutions. This research is intended for the government and Islamic financial institutions to improve education and outreach programs to expand the use of Islamic financing for MSMEs. Thus, it is hoped that MSMEs in Madura can develop more optimally and effectively.